Morphofunctional parameters as predictors of autologous hematopoietic stem cell transplantation outcomes - Cornago, Javier; Dassen, Carolina; Calderón, Cristina; Mahíllo, Ignacio; Pardo, Laura; López-Lorenzo, José Luis; Hormigo, Ana Isabel; Caballero, Juan Carlos; Domingo-González, Amalia; Capellán, Raquel; Iturrate, Isabel; de Camino, Begoña Pérez; et al. (Frontiers in Nutrition, 2025)
IntroductionThere is a lack of predictive factors for specific complications in patients who undergo autologous hematopoietic stem cell transplantation. A complete morphofunctional assessment is not usually performed before the procedure. Malnutrition is related to lower survival in cancer patients. Our aim is to identify both risk and protective factors for such complications to refine management and improve outcomes.MethodsWe have implemented the program ‘RHeNutrir’, which involves a systematic malnutrition and sarcopenia screening, as well as a complete nutritional and functional assessment of transplant candidates. We examined the predictive value of different morphofunctional, clinical and analytical parameters in the context of autologous transplantation.ResultsAnemia, respiratory diseases and diabetes mellitus are associated with many complications and should be optimized before transplant. Elevated C-reactive protein and greater fat mass, as inflammatory biomarkers, are related to fever, longer hospitalization, and even death. Bacteremia and intensive care unit admission are associated with higher mortality. However, better muscle strength and greater lean mass on admission are associated with a lower incidence of these complications and higher albumin levels at discharge are related to a lower risk of early readmission.ConclusionBody composition and muscular function studies should be performed in patients who are candidates for this procedure, and prehabilitation and nutritional intervention protocols should be designed to improve outcomes.